Pregnant Women's Knowledge Regarding Healthy Nutrition during pregnancy at Shahid Hama Rash Primary Health Center, Sulaimaniyah, Iraq - Qadir, Shwan Assad; Saeed, Mahabat Hassan; Kakabra, Cheeman Salih; Ahmad, Livyar Latif (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: In the antenatal period, the nutritional demand of women upsurges to compensate for physiological and psychological changes and nutritional computations by the growing fetus for energy, macro, and micronutrients. Nutrition knowledge is essential in conscious of ample nutrition intake among pregnant women. Objective: This study aimed to assess pregnant women’s knowledge of healthy nutrition Materials and Methods: The non-probability convenient method was used as the sampling technique in this descriptive study. The process of data collection was continued from 26th July 2022 to 26th September 2022. A hundred women were selected from Shahid Hama Rash Primary Health Center, Sulaimaniyah, Iraq. A well-designed questionnaire was constructed, in which its first part includes sociodemographic characteristics and the second part includes questions regarding participants' knowledge. Results: We showed that 82% of participants had good knowledge, as well as 18% of them, had fair knowledge regarding healthy nutrition. At the same time, none of the pregnant women had poor knowledge. Conclusions: We concluded that most study participants had good knowledge, and no significant association was found between knowledge of pregnant mothers and their sociodemographic variables.
Keywords: Knowledge; pregnant women; healthy nutrition; primary health center